RUMAH MODERASI BERAGAMA DI PTKI MENCETAK KADER MAHASISWA BERKESADARAN DAKWAH BELA NEGARA - Daniel S, Tumpal; Amelia, Siska (Jurnal Ilmiah Pendidikan dan Keislaman, 2025)
Religious moderation creates awareness of national defense. Article 27 Paragraph 3 of the 1945 Constitution mandates that: "Every citizen has the right and obligation to participate in efforts to defend the country. Presidential Decree Number 18 of 2020 concerning religious moderation is a policy direction in managing a dynamic and conducive religious life. The Indonesian Ministry of Religious Affairs followed up on the Presidential Decree by issuing Decree. Director General of Islamic Education No. 897 of 2021 concerning Technical Instructions for Religious Moderation Houses in religious universities. Religious Moderation is expected to be the basis for thinking, behaving, and acting as well as the basis for formulating policies and programs. This study uses a regulative qualitative approach to produce descriptive data that the existence of Religious Moderation Houses is effective in cultivating students with awareness of national defense.